STUDI TINGKAT PENGUASAAN RANGKAIAN SISTEM PENGISIAN (CHARGING SYSTEM) OLEH MAHASISWA PASCA PROSES PEMBELAJARAN MATA KULIAH TEORI KELISTRIKAN OTOMOTIF - Widjanarko, Dwi (Universitas Negeri Semarang, 2008)
Mastering of charging system circuit is regarded to be the most difficult thing instudying engine electrical system. Based on this problem, it is necessary to know thelevel of mastering charging system circuit to overcome the problem. This research isconducted by examining the students programming automotive electrical subject in theend of semester. The research result shows that only 9,76% of students have good andvery good grade with 70% until 100% level of mastering charging system circuitwhereas 90,24% of students have less than 50% level of mastering charging systemcircuit. Thus, it is necessary to apply some teaching and learning methods to improvethe level of mastering charging system circuit.Kata kunci: tingkat penguasaan, rangkaian sistem pengisian, kelistrikan engine